GW24-e0342 Ang II induces capillary formation from endothelial cells via the AT1R-dependent inositol requiring enzyme 1 pathway. (1st October 2013) - Xiang, Wang; Bai, Yong-Ping; Hong, Dan; Gao, Hai-Chao; Li, Ling-Fang; Zhu, Ling-Ping; Sun, Quan; Zhang, Guo-Gang
Abstract : Objectives: Previous studies have demonstrated an important interaction between angiotension II type 1 receptor (AT1R) and angiotension II (Ang II)-induced capillary formation from endothelial cells and vascular endothelial growth factor (VEGF). However, the underlying mechanism remains elusive. Recent studies revealed that the unfolded protein response regulates an angiogenic response by the kidney epithelium during ischaemic stress. Therefore, in the present study, we investigated the effects of Ang II on AT1R-mediated capillary formation from endothelial cells and the possible involvement of the IRE1/JNK/p38 MAPK pathway. Methods: Capillary formation from endothelial cells was measured in the Matrigel assay. The phosphorylation of IRE1, JNK and p38 MAPK, expression of VEGF and GRP78 were measured by western-blot. Results: Our results show that Ang II (1 nmol/L) induced the expression of VEGF and enhanced capillary formation from endothelial cells in the Matrigel assay. This effect was significantly depressed by the AT1R blocker losartan and different inhibitors (irestatin, IRE1 specific inhibitor; SP600125, JNK specific inhibitor; SB203580, p38 MAPK specific inhibitor) but not by the AT2R blocker PD123319. Next, we investigated the effect of Ang II on the IRE1/JNK/p38 MAPK pathway and the 78 kilodalton glucose regulated protein 78 (GRP78) activity in HUVECs and the role of the AT1 Receptor. The results show that Ang II activated both the IRE1/JNK/p38 MAPK pathway and GRP78 binding activity. These effects were markedly inhibited by the AT1R blocker losartan. The IRE1 specific inhibitor irestatin, the JNK specific inhibitor SP600125, and the p38 MAPK specific inhibitor SB203580 significantly inhibited Ang II-induced capillary formation from endothelial cells and VEGF expression but had no effect on GRP78. Conclusions: Collectively, these findings suggest for the first time that Ang II promotes capillary formation by inducing the expression of VEGF via Ang II type 1 receptor-mediated stimulation of the IRE1/JNK/p38 MAPK pathway.